1995
DOI: 10.3171/jns.1995.83.2.0237
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcome after lesionectomy for cavernous malformations

Abstract: Cavernous malformations that are associated with seizures are often treated by surgical resection consisting of lesion removal, "lesionectomy," alone. Through retrospective analysis the authors have examined some factors that may predict failure to eradicate seizures by such a procedure. A group of 51 patients were examined who had been treated for supratentorial cavernous malformations with preoperative seizures and received postoperative follow up lasting at least 1 year. There was one mortality in the group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
135
4
5

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(151 citation statements)
references
References 27 publications
7
135
4
5
Order By: Relevance
“…Whereas favorable results and percentages of seizure-free patients as high as 82% have been reported after lesionectomy alone (28,29), improved seizure control after exact delineation and resection of the epileptogenic zone has been emphasized by other investigators (30-33). These data indicate that in patients with solitary circumscribed intracerebral lesions, such as solitary cavernomas, gangliogliomas or gliomas, or localized trauma, the zone of seizure origin very probably is either contiguous with or in close proximity to the lesion (30,34).…”
Section: Discussionmentioning
confidence: 96%
“…Whereas favorable results and percentages of seizure-free patients as high as 82% have been reported after lesionectomy alone (28,29), improved seizure control after exact delineation and resection of the epileptogenic zone has been emphasized by other investigators (30-33). These data indicate that in patients with solitary circumscribed intracerebral lesions, such as solitary cavernomas, gangliogliomas or gliomas, or localized trauma, the zone of seizure origin very probably is either contiguous with or in close proximity to the lesion (30,34).…”
Section: Discussionmentioning
confidence: 96%
“…Longer seizure history and increased number of preoperative seizures are consistent with more difficulty in treating epilepsy with simple lesionectomy surgery 28 . We believe these patients should have a complete epilepsy evaluation to a possible extended surgery guided by electrocorticography.…”
Section: Supratentorial Cavernomas Associated With Seizure (G3)mentioning
confidence: 99%
“…In a series of patients submitted to lesionectomy of supratentorial CMs, a strict relationship was found between the duration of seizure history before the surgical treatment and the cure of epilepsy with the surgery. Cohen et al 28 showed that all patients that presented one preoperative seizure or less than two months of history did not have any seizures after surgery; 75.0 to 80.0% of patients with two to five preoperative seizures or 2 to 12 months of history also had not any seizure after surgery. In addition, 50% of patients with more than five seizures or more than 12 months of history were postoperatively seizure free 28 .…”
Section: Supratentorial Cavernomas Associated With Seizure (G3)mentioning
confidence: 99%
See 2 more Smart Citations